Grammar Software + - Gamao, Austere Rex (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
This is a suite of posthuman poetry that asks the questions: What if everyone is gone and all that is left is the software we created in the cloud and the animals that survived? What does it mean to be ungrammatical? What is the new shape of language when it has become obsolete? The poems seek to engage with the English language as a colonizing instrument and how we have made it our own.